Religulous - Charles, Larry, 1956-; Maher, Bill. (Santa Monica, CA : Lionsgate, 2008)
Comedian and TV host Bill Maher takes a pilgrimage across the globe on a mind-opening journey into the ultimate taboo: questioning religion. Meeting the high and low from different religions, Maher asks questions, like 'Why is faith good?' and more.
Special features: commentary with Bill Maher and director Larry Charles; deleted scenes with commentary by Bill Maher and Larry Charles.
Director of photography, Anthony Hardwick ; edited by Jeffrey M. Werner, Jeff Groth, Christian Kinnard.
Bill Maher, interviewer.
DVD, Dolby digital.
In English with optional English or Spanish subtitles.
Keywords: God; Religion; Faith; Belief and doubt; Documentary films; Video recordings for the hearing impaired